2017
DOI: 10.2340/16501977-2234
|View full text |Cite
|
Sign up to set email alerts
|

Do clinical assessments, steady-state or daily-life gait characteristics predict falls in ambulatory chronic stroke survivors?

Abstract: Independent of the type of gait assessment, qualitative gait characteristics are better fall predictors than clinical assessments. Clinicians should therefore consider gait analyses as an alternative for identifying fall-prone stroke survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 32 publications
4
71
0
Order By: Relevance
“…Data analysis for determining steady-state gait characteristics was consistent with our previous study 9 . Briefly, participants walked on the GRAIL treadmill.…”
Section: Steady-state Gait Characteristicssupporting
confidence: 79%
See 2 more Smart Citations
“…Data analysis for determining steady-state gait characteristics was consistent with our previous study 9 . Briefly, participants walked on the GRAIL treadmill.…”
Section: Steady-state Gait Characteristicssupporting
confidence: 79%
“…The gait events foot contact (FC) and foot off (FO) were determined using the Center of Pressure (CoP) 14 . Gait characteristics like; spatio-temporal, variability and local divergence exponent were determined using 60 consecutive strides 9 .…”
Section: Steady-state Gait Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A group of twenty-nine stroke survivors derived from a larger cohort [15] participated in the obstacle crossing task. After a six-month follow up, twelve stroke survivors (41%) reported at least one fall, and were classified as fall prone stroke survivors (F).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the main aims of the present experiment were to assess test-retest reliability of characteristics of virtual obstacle crossing and assess differences between stroke survivors who experienced falls or no falls. We note here that the data reported were obtained from participants of a previous study that found that steady-state gait characteristics were associated with fall risk [15].…”
Section: Introductionmentioning
confidence: 96%